Kurangnya Fasilitas Sekolah dan Dampaknya terhadap Proses Belajar Mengajar di SMA Muhammadiyah 18 Sunggal - Ujung, Amiruddin; Ruslan, Muhammad (Journal of Sustainable Education, 2025)
This study aims to analyze the lack of school facilities and its impact on the teaching and learning process at Muhammadiyah 18 Sunggal High School. The background of this study is based on the importance of educational facilities as a support for effective learning. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that limited facilities such as classrooms, science and computer laboratories, libraries, sports facilities, and digital learning media have a significant impact on teaching and learning activities. For students, this condition reduces learning motivation, limits practical skills, and impacts learning outcomes. For teachers, limited facilities hinder the use of varied and technology-based learning methods. Meanwhile, for the school, the lack of facilities has an impact on the institution's image and academic climate. The conclusions of this study emphasize the need to improve school facilities through collaboration between the school, foundation, committee, alumni, and the government to support the achievement of optimal educational quality.